Experience of Radical Radiotherapy for Patients with Stages I-III Squamous Cell Carcinoma of the Glottic Larynx - Haque, Md Nizamul; Mostafa, Sk Golam; Chowdhury, Qamruzzaman; Uddin, Mokles; Hussain, Syed Akram; Hasan, Dewan Mahmud (Faridpur Medical College Journal, 2016)
This study was carried out from May 2012 to April 2013, on short term effects of Radical Radiotherapy for patients with Stages I-III squamous cell carcinoma of the glottic larynx at National Institute of Cancer Research and hospital, Mohakhali, Dhaka. A total of 50 biopsy proved squamous cell carcinoma of the glottis larynx were treated with radical Radiotherapy, total dose of which was 66Gy in 33 fractions over 7 weeks, conventionally fractionated with 200 cGy per fraction, one fraction per day and 5 fractions per week, using the machine 6 MV LINAC. The main outcome variables of the study were toxicities and clinical outcome of the patients. The peak age incidence was found in the age group of 51-60 years (56%). Among 50 patients, there were 82% males and 18% females and male to female ratio was 4.6:1. There were 86% found smokers and rests of the 14% patients were non smoker. Treatment related haematological and non-haematological acute and delayed toxicities were studied. Mucosities 28% (grade-II), skin reaction 78% (grade-II), anaemia 52% (grade-II), dysphagia 70% were the most common acute toxicities where as xerostomia 16% was the delayed side effect. With this treatment protocol, 86% patients responded completely. Faridpur Med. Coll. J. Jul 2015;10(2): 63-67